Signal analysis to detect water tree location in polymeric underground cables - Kuan T.M.; Mohd Ariffin A.; Sulaiman S. (2023)
This paper discusses the analysis of signals generated from a set-up to detect water tree location in polymeric underground cables using PSpice simulation tool. The set-up is executed by implementing the time domain reflectometry (TDR) method in analysing the signals. To locate the water tree in a cable, signals are generated from both ideal and degraded XLPE cables due to water treeing. All results are then compiled, analysed and discussed further in this paper to study how water trees can be located along the cable using this method. 2011 IEEE.